Dueling Definitions of Abortifacient: How Cultural, Political, and Religious Values Affect Language in the Contraception Debate - Horner, Claire (The Hastings Center report, 2020)
Contraception works by preventing fertilization of an egg or preventing implantation of a fertilized embryo. For those who believe pregnancy begins at implantation, contraceptives preventing implantation are not abortifacient. However, for those who assert that pregnancy begins at fertilization, any agent causing the intentional loss of an embryo, even prior to implantation, is abortifacient, both morally and for lack of a different term to describe the postfertilization, preimplantation loss. In the debate on this topic, much of the discourse on both sides wrongly focuses on the opposing side's perceived ignorance in denying scientifically proven definitions rather than on the substance of the conflict. Indeed, both sides accuse the other of prioritizing its “subjective” views over “objective” facts. In this essay, we unpack the scientific, cultural, and religious factors that underlie this debate. We argue that the only way to move forward is to clarify our terminology and engage with the substance of the argument, rather than merely the rhetoric.